Incidence of Herpes simplex Virus Infection in Patients with Acute Central Nervous System Infections - Kriss Pérez; Leticia Porto Espinoza; Raimy Mindiola; Diana Callejas; Jesús Estévez; Reyna Moronta (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2010)
Herpes simplex viruses are agents responsible for a variety of infections on buccal and genital mucosa; they are neurotropic, capable of lodging in the nerve cells and remaining latent with subsequent reactivations; in some cases, they can provoke meningitis and encephalitis; and they have a significant morbidity and are associated with a high mortality. The present project aims to determine HSV's effect on the etiology of acute central nervous system (CNS) syndromes using the detection of specific antibodies in serum and cerebrospinal fluid. The 93 paired samples from patients with neurological affectations studied demonstrated negative results in the LCR bacteriological study and their Alb-LCR/Alb-serum relation was < 0.0075. Antibodies were detected by the enzymatic immunoassay ELISA method, where 1.2% (1/93) of the serum samples turned out positive for IgM; 89.24% (83/93) of the serum samples resulted positive for IgG; and 27.39% (20/93) of LCR samples were positive for anti-IgG. IgG presence in LCR suggested the intrathecal production of these antibodies inside the CNS, which demonstrates a significant participation by this viral agent in infections and diseases associated with the CNS.